The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/advs.202304284
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Plumber Reshapes Glymphatic‐Lymphatic System to Sustain Microenvironment Homeostasis and Improve Long‐Term Prognosis after Traumatic Brain Injury

Shiqiang Tong,
Laozhi Xie,
Xiaoying Xie
et al.

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. Long‐term changes in the microenvironment of the brain contribute to the degeneration of neurological function following TBI. However, current research focuses primarily on short‐term modulation during the early phases of TBI, not on the critical significance of long‐term homeostasis in the brain microenvironment. Notably, dysfunction of the glymphatic‐lymphatic system results in the accumulation of danger/damage‐associated mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Developing a nano‐plumber that coencapsulates the microenvironment regulator pro‐DHA and the lymphatic‐specific growth factor VEGF‐C, Chen et al significantly improves the neurological function of rodents with traumatic brain injury through enhanced glymphatic‐lymphatic drainage, suppressed microglia and astrocytes activation. [ 31 ] Overexpression of VEGF‐C improves clearance of senescent astrocytes and mitigates neuroinflammation. [ 32 ] Notably, VEGF‐C also shines a light on brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Developing a nano‐plumber that coencapsulates the microenvironment regulator pro‐DHA and the lymphatic‐specific growth factor VEGF‐C, Chen et al significantly improves the neurological function of rodents with traumatic brain injury through enhanced glymphatic‐lymphatic drainage, suppressed microglia and astrocytes activation. [ 31 ] Overexpression of VEGF‐C improves clearance of senescent astrocytes and mitigates neuroinflammation. [ 32 ] Notably, VEGF‐C also shines a light on brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MRI of a closed-head impact model of engineered rotational acceleration (CHIMERA) shows meningeal enhancement 7d after single and repeat injury, reflecting clinical observations [ 305 ]. Controlled cortical impact (CCI) in mice presents mixed findings: Lyve-1 + morphology is increased at 7 d (impact 1.5 mm) [ 306 ], with contrasting studies showing decreases at 3 d (impact 2 mm) [ 307 ], and 1 month (impact undisclosed) [ 308 ], highlighting the nuanced and variable nature of spontaneous lymphangiogenic responses across varied mechanisms of impact and injury parameters. Regardless, if plasticity of the lymphatic network can be induced, it may be beneficial to improve outcomes (Fig.…”
Section: Meningeal Lymphatic Dysfunction After Tbimentioning
confidence: 99%
“…2 ). Indeed, across models of TBI, overexpression of VEGF-C drives lymphangiogenesis, enhances functional drainage and improves injury induced neurological deficits, including those seen in aged animals [ 303 , 304 , 306 , 308 310 ].…”
Section: Meningeal Lymphatic Dysfunction After Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…Following injury, the rate of paravascular drainage is slowed by as much as 60%, causing a subsequent reduction in the movement of interstitial fluid through the brain and an increase in protein accumulation in the parenchyma (67). Furthermore, it has recently been shown that enhancement of glymphatic-lymphatic drainage via a "nano-plumber" technology results in a significant improvement in neurological function in rodents following TBI (68). This treatment works by returning injured tissue to a homeostatic microenvironment via dampening the local microglial response and recovering healthy vascular and glymphatic-meningeal lymphatic circulation to support the clearance of noxious material and pro-inflammatory immune cells.…”
Section: Glymphatic-meningeal Lymphatic Circulationmentioning
confidence: 99%